Occurrence and feeding preference of Diabrotica speciosa Germar and Cerotoma arcuata (Olivier) for different cultivars of cowpea Vigna unguiculata (Linnaeus) Walpers - de Souza, Danival José; Pachoute, Julner (EntomoBrasilis, 2019)
Abstract. Chrysomelid pests are not only known as leaf-feeding in beans but as vectors of viruses too. Chemical control is most commonly used but has high economic and environmental costs. This study aimed to report the occurrence of chrysomelid pests on cowpea area in the State of Tocantins and compare the feeding preference of the species collected in different cowpea cultivars. Weekly monitoring was carried out in cowpea stand at the experimental station of the Federal University of Tocantins, in Gurupi-TO. Insect feeding preference was evaluated under laboratory conditions (25 ± 2 °C, 60 ± 5% R.H.). A total of 1,542 adults of two species of chrysomelid pests was recorded: Cerotoma arcuata (Olivier) presented 71.49% and Diabrotica speciosa Germar, 28.51%. Leaf discs of the cultivars BRS "Tumucumaque"," BRS "Nova Era", BRS "Sempre Verde", and "Pingo de Ouro", were offered to adult beetles. It was observed a significant difference in no-choice leaf disc assays and four-choice leaf disc assays for the D. speciosa species, being BRS "Tumucumaque" the most consumed. In the no-choice leaf disc assay "Pingo de Ouro" was less consumed and showed non-preference type resistance. In the four-choice leaf disc assay, BRS Sempre Verde was more resistant to D. speciosa consumption. In both tests, C. arcuata did not show a significant difference among the tested cultivars, but mathematically, BRS "Nova Era" was the most consumed, while "Pingo de Ouro" the lowest consumed and showed non-preferred resistance in both tests. Cerotoma arcuata stood out as greater defoliant than D. speciosa in all cultivars tested. Ocorrência e preferência alimentar de Diabrotica speciosa Germar e Cerotoma arcuata (Olivier) por diferentes cultivares de feijão caupi Vigna unguiculata (Linnaeus) Walpers Resumo. Crisomelídeos pragas não são apenas desfolhadores do feijoeiro, mas atuam também como vetores de viroses. O método de controle mais utilizado é o químico, o que acarreta altos custos econômicos e ambientais. Este trabalho objetivou registrar a ocorrência de crisomelídeos pragas em cultivo de feijão-caupi no estado do Tocantins, bem como comparar a preferência alimentar das espécies coletadas por diferentes cultivares. Foi realizado monitoramento semanal na área de feijão-caupi da estação experimental da Universidade Federal do Tocantins em Gurupi-TO. Foram registrados 1.542 adultos de duas espécies de crisomelídeos pragas: Cerotoma arcuata (Olivier)apresentou 71,49% e Diabrotica speciosa Germar, 28,51%. Em condições de laboratório, discos foliares das cultivares BRS "Tumucumaque", BRS "Nova Era", BRS "Sempre Verde" e "Pingo de Ouro" foram oferecidos a insetos adultos para testar sua preferência alimentar. Foi observada diferença significativa nos ensaios sem chance e com chance de escolha para espécie de D. speciosa, sendo o BRS "Tumucumaque" o mais consumido. Nos ensaios sem chance de escolha, "Pingo de Ouro" foi menos consumido e apresentou resistência do tipo não preferência. Nos ensaios com chance de escolha, o cultivar BRS "Sempre Verde" foi mais resistente ao consumo de D. speciosa. Em ambos os testes, C. arcuata não apresentou diferença significativa na preferência pelos quatro cultivares, embora BRS "Nova Era" tenha sido mais consumido em valores absolutos, enquanto "Pingo de Ouro" foi menos desfolhado apresentando resistência de tipo não preferência nos dois testes. Cerotoma arcuata destacou-se como maior desfolhador do que D. speciosa em todas os cultivares testados.